Analysis of Willingness to Pay for Ancillary Revenue of Full Service Airline (The Case of Garuda Indonesia) - Klislinar , Ermila; Wachidin Widjaja, Anton (KnE Social Sciences, 2020)
Airlines are facing challenges from high cost structures and intense competition. This has made airlines universally look for opportunities to generate ancillary revenue, additional income apart from their main sources, including Full Service Carriers (FSC). Measuring consumer’s willingness to pay is pivotal in pricing and estimating ancillary revenue demand. This study analyzes whether customer’s type of journey, purpose of journey, length of flight, and type of flight class have an impact on willingness to pay (WTP) of Garuda Indonesia’s ancillary revenues which comprises of unbundled products and commission-based income. This paper uses data from a survey to Garuda Indonesia’s customer and follows quantitative studies to identify and describe the relationship between the WTP of Garuda Indonesia’s ancillary revenue and all variables involved. The study found that passengers value more the unbundled products. It is also found differences in WTP for particular ancillary products and services based on purpose of journey, length of flight, and type of flight class. Keywords: Ancillary Revenue, Willingness to Pay, Type of Journey, Length of Flight, Journey Purpose, Type of Cabin Class, Full Service Carriers